Paradigma Bela Negara dalam Surat An-Naml Ayat 1-66: Representasi Akronim Kata “AN-NAML” - Adi Supardi; Sona Zainal Walad; Mida Hardianti; Ikbal Sabarudin; Hamid Sidiq (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This research wants to describe the actualization of the state defense paradigm in the Qur'an. The concept is offered using the AN-NAML acronym, namely Attitude; Nationalism; nature; associations; manage; and Lovely. The AN-NAML concept is sourced from the contents of the letter An-Naml verses 1-66. The method used is descriptive qualitative through contextual analysis of the text of the verse, then finding correlations so that it can be applied as a standard of values ​​and knowledge. The results of this study indicate that the AN-NAML concept can help provide information on new findings and structured efforts to help the government actualize Al-Qur'an values ​​in the field of instilling state defense values. Attitude as a spiritual foundation, Nationalism as love for the motherland, Nature as an objective behavior, Association is able to socialize and work together, Manage has leadership, and Lovely so that love becomes the basis of attitude and speech.